Developing Pairwise Preference-Based Personality Test and Experimental Investigation of Its Resistance to Faking Effect by Item Response Model. Issue 4 (1st October 2016) - Usami, Satoshi; Sakamoto, Asami; Naito, Jun; Abe, Yu
Abstract : Recent years have shown increased awareness of the importance of personality tests in educational, clinical, and occupational settings, and developing faking-resistant personality tests is a very pragmatic issue for achieving more precise measurement. Inspired by Stark (2002) and Stark, Chernyshenko, and Drasgow (2005), we develop a pairwise preference-based personality test that aims to measure multidimensional personality traits using a large-scale statement bank. An experiment compares the resistance of the developed personality test to faking with that of rating scale-based personality tests in the item response theory model framework. Results show that latent traits estimated from the personality test based on the rating scale method are severely biased, and that faking effect can be pragmatically ignored in the personality test developed based on the pairwise preference method.